2021
DOI: 10.3390/ani11040946
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Forage Mixtures of Ryegrass (Lolium spp.) with Clover (Trifolium spp.) Supplemented with Local Feed Diets to Reduce Enteric Methane Emission Efficiency in Small-Scale Dairy Systems: A Simulated Study

Abstract: In cattle, greenhouse gas (GHG) emissions and nutrient balance are influenced by factors such as diet composition, intake, and digestibility. This study evaluated CH4 emissions and surpluses of crude protein, using five simulated scenarios of supplementation in small-scale dairy systems (SSDS). In addition, two pasture managements (cut-and-carry versus grazing) and two varieties of legumes (red clover vs. white clover) were considered. The diets were tested considering similar milk yield and chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(94 reference statements)
0
2
1
1
Order By: Relevance
“…It is known that there is a directly proportional relationship between milk yield and the amount of fat in milk, according to data from INRA (2007), which mentions that 2 g/kg of fat is reduced with an increase of 10 kg of milk, which may explain why the fat content results of Arjona-Alcocer et al (2020) are different from those found in this work, and are also different from the data reported by Barros et al (2017) in Arlington, Wisconsin who found that in Holstein cows with 11.8% CP diets the fat levels were 43.4 g/kg, lactose 46.9 g/kg and protein 33.3 g/kg. It also differs with Celis-Alvarez et al (2021) who reported values for fat as 38.2 and 38.8 g/kg and for protein as 29.03 and 28.79 g/kg in a small-scale milk production system in the central plains of Mexico.…”
Section: Resultscontrasting
confidence: 88%
“…It is known that there is a directly proportional relationship between milk yield and the amount of fat in milk, according to data from INRA (2007), which mentions that 2 g/kg of fat is reduced with an increase of 10 kg of milk, which may explain why the fat content results of Arjona-Alcocer et al (2020) are different from those found in this work, and are also different from the data reported by Barros et al (2017) in Arlington, Wisconsin who found that in Holstein cows with 11.8% CP diets the fat levels were 43.4 g/kg, lactose 46.9 g/kg and protein 33.3 g/kg. It also differs with Celis-Alvarez et al (2021) who reported values for fat as 38.2 and 38.8 g/kg and for protein as 29.03 and 28.79 g/kg in a small-scale milk production system in the central plains of Mexico.…”
Section: Resultscontrasting
confidence: 88%
“…The silage samples were dried at 65 °C for 48 h in a forced draught oven for dry matter (DM) content analysis, and following the procedures described by Celis-Álvarez et al (2021), their neutral detergent fiber (NDF), acid detergent fiber (ADF), and crude protein (CP) contents were determined. In vitro dry matter digestibility (IVDMD) was determined by the microbag technique with ruminal liquor in an Ankom Daisy fermenter (ANKOM, 2005), and the estimated metabolizable energy (eME) content was calculated using the equation proposed by CSIRO (2007):…”
Section: Variables Evaluatedmentioning
confidence: 99%
“…El estudio se realizó mediante un experimento en finca, siguiendo los lineamientos de investigación participativa rural (Conroy, 2005) y contó con la colaboración de un productor de leche en pequeña escala del municipio de Aculco, Estado de México (20° 06' N y 99° 52' W; 2440 m). El clima en la región es templado sub húmedo, con temperatura mínima promedio de 7 ºC y máxima de 24 ºC; y 890 mm de precipitación anual (Celis-Álvarez et al, 2021).…”
Section: Desarrollo Experimental Y áRea De Estudiounclassified